Semblance Of Ayurveda In Cerebral Palsy - Dixit , Megha; Jangid, Sushil Kumar (International Research Journal of Ayurveda & Yoga, 2024)
Cerebral palsy is one among the most common childhood disabilities, which cripple and hamper the development of a child. It is ubiquitous and it occurs all around the world, causing considerable hardship to affected individuals and their families. It is not a single disease but a name given to wide variety of static neuromotor impairments syndrome occurring secondary to a lesion in the developing brain. Cerebral Palsy is not curable. Several advances in its management and research are going in various parts of world with goal to improve the physical and functional status of the CP child.Cerebral palsy cannot be co-related with any single disease or condition in Ayurveda as it is a multifactorial condition. All most all major neurological disorders are identified with Vatadosha. So, considering the classification and their respective features, Cerebral Palsy can be compared to Vatavyadhi or Vikara, which may manifest itself in any form like Pakshaghata, Ekangavata, Pangu, Sarvangavata, Kampavata etc., and diagnosis is based on the lakshanas. Cerebral palsy may also be considered as Shiromarmabhighatajavatavyadhi as caraka while describing Shiromarmabhighataja has mentioned vatavikaras like Chestanasa (loss of motor activities), Hanugraha, Mukatva(dumbness), Gadgadatva, Lalasrava, Svarahani(aphasia)etc., and marmaaghata is one of the causes of vatavikara.1 The main causative factor is vata and all the acharyas including Kashyapa have mentioned vasti karma as the best line of treatment in alleviating vitiated vata. Vasti provides strength, particularly in children and aged people. Vasti is very important, as it radically expirates the morbid vata, the sole dosharesponsible for the movements of all doshas, dhatu and mala within the body. Charaka aptly highlighted Vasti - as Vastivataharanamshreshtha.2 Vasti indeed is the half of the entire management of diseases. Vasti increases Agni, Medha, and Varna etc.In Cerebral palsy, as the main etiology is damage to the brain, so along with shodanachikitsa a group of Medhya drugs, vataharadrugs are used. AcharyaKashyapa had mentioned many Medhyarasayanas among which Yastimadhu, Vacha, Brahmi, Ashwagandha.3